Synergistic effect of boron nitride and graphene nanosheets on behavioural attitudes of polyester matrix: Synthesis, experimental and Monte Carlo simulation studies - Basgo, Oykum; Guler, Seval Hale; Guler, Omer; Canbay, Canan A.; Zakaly, Hesham M. H.; Issa, Shams A. M.; Tekin, H. O. (Elsevier Science Sa, 2022)
We report the synergistic effects of boron nitride and graphene nanosheets on physical, structural, and nuclear radiation attenuation properties of polyester matrix-incorporated nanocomposites. Some critical material properties are thoroughly evaluated for several types of synthesized samples. Polyester is employed to strengthen graphene and boron nitride nanolayers, and their characteristics are investigated in detail. Additionally, we report the gamma-ray and fast neutron attenuation characteristics of synthesized nanocomposites to get a better understanding of the reinforcing effect as a function of material type and weight percentage. Thermal analysis findings indicate that adding graphene lowers the decomposition temperature but co-adding graphene and BNNS enhances thermal decomposition in comparison to graphene itself. Tensile tests showed that the inclusion of both GRP and GRP/BNNS strengthens the material. Among the polyester composite samples analyzed, the G3 sample with the most GNP reinforcement had the lowest HVL values throughout the broadest range of energy levels investigated. The recent findings may be beneficial to the scientific community in terms of incorporating these reinforcing types and ratios into polyester materials for a variety of applications, including industrial and research purposes.
Keywords: Boron nitride; Graphene; Nanocomposites; Thermal properties; SEM; FLUKA